Making Sense of One Dollar CEO Salaries - Hamm, Sophia J. W.; Jung, Michael J.; Wang, Clare (Contemporary Accounting Research, 2015)
Abstract We examine the determinants and outcomes of Chief Executive Officers ( CEO s) accepting a $1 salary, a compensation practice that occurs relatively frequently in high‐profile firms and is debated by regulators, investors, and the media. Using a hand‐collected sample of 93 CEO s from 91 firms between 1993 and 2011, we examine the triggers preceding the $1 salary decision, the factors associated with the decision, subsequent stock returns, and the outcomes for the CEO s. Our evidence is consistent with two explanations for the phenomenon: (i) it is a gesture of sacrifice by CEO s of firms in crisis, and (ii) it is a signal of better future performance by CEO s of growing firms. Our analyses highlight the two different circumstances and shed light on an interesting debate that has thus far been supported only by anecdotal evidence.